2015
DOI: 10.3390/w7020377
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Comprehensive Fouling Model for a Rotating Membrane Bioreactor System Treating Wastewater

Abstract: Membrane bioreactors (MBRs) are now main stream wastewater treatment technologies. In recent times, novel pressure driven rotating membrane disc modules have been specially developed that induce high shear on the membrane surface, thereby reducing fouling. Previous research has produced dead-end filtration fouling model which combines all three classical mechanisms that was later used by another researcher as a starting point for a greatly refined model of a cross flow side-stream MBR that incorporated both hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 25 publications
7
15
0
Order By: Relevance
“…Jiang et al [127] demonstrated that rotating flat-sheet MBR have a slower fouling rate compared to conventional MBRs when consuming the same energy. Paul and Jones [131] estimated through the modelling studies that, the rotation efficiency in terms of fouling prevention was 12%, suggesting that prevention of cake build-up and fouling is mostly accomplished by air scouring. Various types of rotation MBRs are currently available on the MBR market as commercial products, including a cross-flow MBR system with rotating ceramic discs impellers Grundfos BioBooster [132] and Huber vacuum rotation membrane VRM® bioreactor [133].…”
Section: Membrane Fouling Controlmentioning
confidence: 99%
“…Jiang et al [127] demonstrated that rotating flat-sheet MBR have a slower fouling rate compared to conventional MBRs when consuming the same energy. Paul and Jones [131] estimated through the modelling studies that, the rotation efficiency in terms of fouling prevention was 12%, suggesting that prevention of cake build-up and fouling is mostly accomplished by air scouring. Various types of rotation MBRs are currently available on the MBR market as commercial products, including a cross-flow MBR system with rotating ceramic discs impellers Grundfos BioBooster [132] and Huber vacuum rotation membrane VRM® bioreactor [133].…”
Section: Membrane Fouling Controlmentioning
confidence: 99%
“…Each membrane sheet in disc form was composed of hydrophilic, low fouling polyvinylidene fluoride (PVDF) polymer with the manifold that collected the permeate flow being located in the single shaft. The measurements of TMP, dissolved oxygen levels, temperature, pH, permeate flux, air scouring flow rates, viscosity and MLSS concentration were all covered in detail in Paul and Jones [ 17 ]. Figure 2 shows part of the set-up of this research rig in operation.…”
Section: Methodsmentioning
confidence: 99%
“…Using the Brookfield rotating viscometer [ 17 ] that also acted as a rheometer, measurements were taken following protocols in-line with Yang et al [ 20 ] and Ratkovich et al [ 21 ]. The proprietary software program for this apparatus was used for system control and collection of data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jiang et al confirmed that rotating flat sheet MBRs result in lower fouling potential than with conventional MBRs with the same energy consumption. A critical speed of 60 rpm was suggested by Wu et al In another study, Paul and Anderson Jones observed that the contribution of rotation in fouling reduction is only 12 %, while air scouring has more influence on fouling.…”
mentioning
confidence: 99%